A multi-broadcast communication system for high dynamic vehicular ad-hoc networks. (15th December 2011) - Lehner, Andreas; Rico-Garc?a, Cristina; Strang, Thomas
The implementation of safety-of-life services in transportation systems, e.g. for applications like collision avoidance of vehicles, requires reliable and instantaneous information exchange. In this paper, we present the design of an infrastructure-less ad-hoc inter-vehicle communication system that fulfils these requirements with respect to the boundary conditions in the railway environment, where a limited communication range and relatively high speeds of nodes cause the network to be highly dynamic. Moreover, in areas with high user densities the common media access is a challenge due to limited bandwidth and interference from other wireless systems.